Paeoniflorin Improves Cardiac Function and Decreases Adverse Postinfarction Left Ventricular Remodeling in a Rat Model of Acute Myocardial Infarction [Corrigendum] - Chen H; Dong Y; He X; Li J; Wang J (Dove Medical Press, 2020)
Chen H, Dong Y, He X, Li J, Wang J. Drug Des Devel Ther. 2018;12:823–836. The authors have advised Figure 11D on page 833 is incorrect. Due to an error at the time of figure assembly Figure 10D and Figure 11D were duplicated. The correct Figure 11 is shown below. The authors apologize for this error and advise it does not affect the results of the paper. Read the original article